Antibacterial Activities of Yansoon (Pimpinella anisum L.), Ginger (Zingiber officinale L.) and Cinnamon (Cinnamomum zeylanicum L.) Extracts - Abdalla, Mai A.; Abuelhassan, Nahla O.; Abdel Rahim2, Awad M. (Gezira Journal of Engineering and Applied Sciences; مجلد 14 عدد 1 (2019), 2019)
There is a n increasing demand for the biologically active substances from plant origin which is of current interest and focus for new research approach. The synthetic pharmaceuticals compounds showed various side effects on functions of different parts of the human body, both internally and externally. Therefore, the present study was investigating the antimicrobial activity of three important herbs, Ginger ( Zingiber officinale L.), Yansoon ( Pimpinella anisum L . ) and Cinnamon ( Cinnamomum zeylanicum L.). The cup- plate agar (inhibition zone) method was used for studying the effects of the extracts against Streptococcus sp , Staphylococcus aureus and  Enterococcus faecalis. The results showed that, the ethanol extracts of cinnamon and the combination of ginger and cinnamon were highly effective on Streptococcus sp (24mm and 21mm, respectively), compared to the water extracts (15mm and16mm, respectively). However, the water and the ethanol extracts of ginger and yansoon were less effective (11mm, 9mm, 8.5mm and 8mm, respectively). The ethanol extracts of cinnamon and the combination of ginger and cinnamon were highly effective on Staphylococcus aureus giving (24mm and 21.5 mm, respectively) followed by water extract (20mm and 21 mm, respectively). While, the ethanol and water extracts of ginger and yansoon were less effective (11mm, 10.5mm, 9mm and 9.5mm, respectively). The ethanol and water extracts of cinnamon were highly effective on E. faecalis giving (21mm and 20.5 mm, respectively). The ethanol extracts of the combination of ginger and cinnamon were effective (20 mm) followed by water extract (18mm). The water and ethanol extracts of ginger and yansoon were less effective giving (15 mm, 12 mm, 8 mm and 9 mm, respectively). From the results it could be concluded that, the extracts of (Cinnamon, Yansoon and Ginger) can be used as antimicrobial agents. It could be suggested that the active antimicrobial components need to be verified in any further study and more microorganism are to be tested                                                                                          .